Effectiveness of Consultation on Student Ratings Feedback: A Meta-Analysis - Penny, Angela R.; Coe, Robert (Review of Educational Research, 2004)
Consultation on student ratings is recognized as an important strategy to support university teachers in learning from student ratings feedback. However, there is little evidence to suggest which practices and strategies are most important for successful consultation. As the use of student ratings increases, such evidence becomes increasingly important. The authors of this article performed an exploratory meta-analysis to determine the effects of various consultation strategies and to identify the conditions under which consultative feedback is most effective in improving teaching effectiveness. The results indicated that the various approaches to consultation are not equally effective. The authors suggest that only with use of certain consultation strategies might the benefits of support with student ratings feedback be maximized.